Interpretasi Pola Penyebab Hama Virus Unggas pada Ayam dengan Pendekatan Bioinformatika (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
The application of bioinformatics in this research provides deeper insight into mutation patterns and virus spread in chickens. Phylogenetic models and genetic analysis enable the identification of higher risk virus strains, as well as understanding how high risk viruses can adapt to their host environment. Avian Influenza or bird flu is a disease caused by viruses including type A influenza virus which can infect poultry, especially chickens. This research aims to determine the interpretation of patterns causing poultry virus pests in chickens using a bioinformatics approach. This research uses a qualitative method with a descriptive approach. Identifying the causes of disease in poultry, especially chickens, using a bioinformatics approach can be done by managing molecular biology data on the birds to be studied, especially DNA sequence and genetic information.